Evaluation of Impact and Transverse Strength of Denture Bases Repaired with Nano Reinforced Resin - Al-Judy, Hikmat J.; Ahmed, Ali N.; Abdul-Razak, Rola W. (Journal of Baghdad College of Dentistry, 2016)
Background: Failure of resin bases were a major disadvantage recorded in the constructed dentures. Reinforcements of the repair joint with nano fillers represent an attempt to enhance the strength and durability. The purpose of the research was to estimate the influence of nano fillers reinforcement with (ZrO2 and Al2O3) on impact and transverse strength of denture bases repaired with either cold or hot processing acrylic resin.Materials and methods: A hundred and forty (140) samples were processed with hot cured resin and organized in subgroups depending on the repair materials and condition (without repair (control), repair with hot cure, cold cure, hot and cold cure reinforced with either (5% Zr2O or 0.5% Al2O3). The samples in these subgroups were processed depending on the test applied (impact and transverse strength). The samples were immersed in distalled water for about four weeks at 37Â°C before testing, after that, the samples prepared for each test were subdivided depending on the selected subgroups of the study. Repairing the samples with cold cure resin was done with the aid of Ivomet; after that the samples incubated for 48 hours in 37Â°C distilled water. Transverse strength test was done by using INSTRON universal testing machine while the impact test was done by using CHARPY impact testing machine.Results: The reinforcement of the repair joint with nano-fillers improves both impact and transverse strengths.Conclusion: Repair strength is directly proportional to the mode of resin processing, reinforcement with nano-fillers improve the strength of the repaired joint significantly.